PENGARUH ECONOMIC VALUE ADDED (EVA), MARKET VALUE ADDED (MVA) DAN ARUS KAS OPERASI TERHADAP RETURN SAHAM PERUSAHAAN LQ-45 - Dona, Rahma; Ermawati, Wita Juwita (MIIPS, 2010)
Buying and selling shares in the capital market is one method to overcomeproblems of liquidity and as a means of investment for those who have excessfunds. Investment in capital markets is one of high liquidity category investments andconvertible (easily converted) so it is important for issuers to consider the interests ofcapital owners that is to maximize firm value.This study intended to determine how the value of Economic Value Added(EVA), Market Value Added (MVA), operating cash flow and stock return and theinfluence of EVA, MVA and operating cash flow on stock return in 33 companies LQ-45index period of August 2009-January 2010 at the BEI. As for investors can be used asrecommendation for investment.The results indicate that the companies have value of positive and negative EVA,positive and negative MVA, all positive operating cash flow, and positive, 0, andnegative stock returns. From the regression equation, EVA has a regression coefficientvalue 0.122, the regression coefficient of MVA has value â 0.227, and the regressioncoefficient of operating cash flow has value 0.221. Test results show that the value ofEVA, MVA, and operating cash flow have no effect significantly on stock returns. This isdue to the absence of capital market efficiency over the stock price, that investors havenot fully use the available information to analyze a particular companys stock. Thusstock prices that occurred, did not reflect actual corporate performance.